World without a Word: Reading Silence in Selected Recent Nigerian Poetry - Adewuyi Aremu Ayodeji (Journal of Language and Literature, 2022)
Trauma is not a recent motif in Nigerian literature. Literary critics have copiously investigated into the trauma of Nigerian Civil War. However, the Boko Haram insurgency, which has ravaged many communities majorly in the North-East of Nigeria, has introduced a new dimension of exploring trauma into Nigerian literature. The literary dimension is patterned around what, in a broad term, may be called ‘trauma of Boko  Haram’. The inability of traumatized Nigerian female victims of the Boko Haram insurgency to unequivocally express the extent of atrocities perpetrated against them by those who should ordinarily be their saviours, confidants or helpers (after the attack) is the main focus of this study. Trauma theory was used to analyse the selected poems taken from a book edited by Ojaide et al. (2019), The Markas: An Anthology of Literary Works on Boko Haram. It was established, on the one hand, that these ‘doubly’ traumatised women are forced to subsist merely in a world of silence – the sole response to the second phase of trauma – by these ‘traumatising tools’. On the other hand, the women’s silence is sustained or prolonged by the subconscious awareness of loss of hopes of recovery. It can be concluded, then, that all the ‘artificial situations or measures’ created to silence the crying voice of the female victims of the Boko Haram insurgency accordingly aggravate their traumatic memory.